Homeopathic treatment of a canine abscess - Ana Catarina Viana Valle; Maria Luiza Viana Valle (Pubvet)
Salivary gland abscesses in dogs are relatively common and often result from bacterial infections secondary to trauma or insect bites.  Conventional treatment typically involves antibiotics and surgical drainage, which can be quite invasive and are often associated with frequent recurrence. However, there is growing interest in integrative therapies, including homeopathy, as less invasive approaches aiming to achieve definitive remission of clinical signs and reduce recurrence in specific cases. This study evaluated the effect of a homeopathic protocol, including Hepar sulphur and Silicea, on a dog diagnosed with a salivary gland abscess. The results demonstrated a significant reduction in lesion size and pain, with no notable adverse effects, suggesting that homeopathy may serve as an effective alternative or complement to conventional treatment.